Kur’an muhtevası bağlamında Kur’an ansiklopedilerinin tahlil ve değerlendirmesi - Karaca, Abdullah (My University, 2019)
Yirminci yüzyılın son çeyreğinden itibaren ortaya çıkan “Kur’ân ansiklopedisi” başlıklı eserlerin sayısı her geçen gün artmaktadır. Bu çalışmada, on tane Kur’ân ansiklopedisi Kur’ân muhtevası açısından incelenmiş ve ansiklopedik bir bakışla nasıl bir Kur’ân muhtevası sergilendiği tespit edilmeye çalışılmıştır. Tez; giriş, üç bölüm, sonuç ve eklerden oluşmaktadır. Girişte konunun çerçevesi netleştirilmiş, birinci bölümde Kur’ân muhtevasına yönelik çalışmalar hakkında bilgi verilmiştir. İkinci bölümde, ele alınan Kur’ân ansiklopedileri tanıtılıp değerlendirilmiş, değerlendirmeye esas teşkil etmeyen diğer ansiklopediler isimleri ile zikredilmiştir. Üçüncü bölümde Kur’ân ansiklopedileri, Kur’ân muhtevası açısından değerlendirilmiştir. Ayrıca klasik dönemin ansiklopedik eserleri ile günümüz Kur’ân ansiklopedileri kıyaslanmıştır. Ekler kısmında, ele alınan ansiklopedilerin Kur’ân muhtevası ile ilgili maddeleri listelenmiştir.Kur’ân ansiklopedileri hem Kur’ân’da geçen kelime, terkip, şahıs, varlık ve konuları hem de Kur’ân’ın ilişkilendirildiği alanları ele alarak birçok madde içermektedir. Bu eserlerdeki maddelerin seçiminde; tefsir faaliyetleri, şer’î ilimler, bilimsel ve sanatsal konular, zanaatlar ve meslekler, sosyal kurumlar, çağdaş akımlar ve düşünceler, güncel sorunlar, Kur’ân etrafındaki tartışmalı meseleler ve diğer kutsal kitaplar ile kıyaslamaların etkisini görmek mümkündür. Hacimli tefsirler ile kapsamlı Kur’ân ilimleri çalışmaları, klasik dönemdeki ansiklopedik eserler olarak değerlendirilebilirler. Günümüz Kur’ân ansiklopedileri ile klasik dönem ansiklopedik eserleri, Kur’ân muhtevasına yönelik ilgi açısından nicel ve nitel farklılıklara sahiptir.

The number of works titled “Encyclopedia of the Qur'an”, that has emerged since the last quarter of the twentieth century, is increasing day by day. In this study, ten number of Qur'anic encyclopedias were examined in terms of the Qur'anic content and it was tried to determine how a Qur'anic content was displayed with an encyclopedic perspective. This thesis consists of introduction, three chapters, conclusion and appendixes. In the introduction, the framework of the subject was clarified and the first chapter gave information about the studies on the content of the Qur'an. In the second chapter, these ten encyclopedias were introduced and evaluated. Besides, encyclopedias other than these ten were mentioned. In the third chapter, these ten works were analyzed and evaluated in terms of the content of the Qur’an. In addition, the encyclopedic works of the classical period and the contemporary encyclopedias of the Qur’an are compared. In the appendixes, the articles of the questioned encyclopedias, relating to the content of the Qur’an, were listed.The encyclopedias of the Qur'an contain a big number of subject that address the Qur’anic words, subjects, figures, entities and passages as well as the areas in which the Qur'an is associated. It is possible to see the effect of the following factors in the selection of these titles in encyclopedias of the Qur’an: Tafsir activities, Islamic sciences, scientific and artistic issues, crafts and jobs, social institutions, contemporary movements and thoughts, current problems, controversial issues around the Qur'an and comparisons with other holy books. Voluminous tafsirs and comprehensive works of the Qur’anic sciences can be considered as encyclopedic works in the classical period. Today's Qur’anic encyclopedias and classical encyclopedic works have quantitative and qualitative differences in terms of interest to the content of the Qur'an.
Keywords: ansiklopedi; Criticism, interpretation, etc; Eleştiri, yorum, vb; encyclopedia; konulu tefsir Encyclopedias of the Qur’an; Kur’ân ansiklopedileri; Kur’ân muhtevası; Kur’n-ı Kerim; Qurʼan; the content of the Qur’an; thematic exegesis